EVALUACIÓN DEL EFECTO DEL PRESECADO MEDIANTE LAS CARACTERÍSTICAS FISICOQUÍMICAS Y SENSORIALES DE CACAO (Theobroma cacao L.) - MORAN RODRIGUEZ, KARLA STEFANIA (2025)
The present study aimed to evaluate the effect of pre-drying on the physicochemical and sensory characteristics of cocoa beans (Theobroma cacao L.) using different fermentation techniques